A cell wall protein-based vaccine candidate induce protective immune response against Sporothrix schenckii infection - Portuondo, Deivys Leandro [UNESP] (2016)
Sporotrichosis is a subcutaneous mycosis caused by several closely related thermo-dimorphic fungi of the Sporothrix schenckii species complex, affecting humans and other mammals. In the last few years, new strategies have been proposed for controlling sporotrichosis owning to concerns about its growing incidence in humans, cats, and dogs in Brazil, as well as the toxicity and limited efficacy of conventional antifungal drugs. In this study, we assessed the immunogenicity and protective properties of two aluminum hydroxide (AH)-adsorbed S. schenckii cell wall protein (ssCWP)-based vaccine formulations in a mouse model of systemic S. schenckii infection. Fractioning by SDS-PAGE revealed nine protein bands, two of which were functionally characterized: a 44 kDa peptide hydrolase and a 47 kDa enolase, which was predicted to be an adhesin. Sera from immunized mice recognized the 47 kDa enolase and another unidentified 71 kDa protein, whereas serum from S. schenckii-infected mice recognized both these proteins plus another unidentified 9.4 kDa protein. Furthermore, opsonization with the anti-ssCWP sera led to markedly increased phagocytosis and was able to strongly inhibit the fungus’ adhesion to fibroblasts. Immunization with the higher-dose AH-adjuvanted formulation led to increased ex vivo release of IL-12, IFN-γ, IL-4, and IL-17, whereas only IL-12 and IFN-γ were induced by the higher-dose non-adjuvanted formulation. Lastly, passive transference of the higher-dose AH-adjuvanted formulation's anti-ssCWP serum was able to afford in vivo protection in a subsequent challenge with S. schenckii, becoming a viable vaccine candidate for further testing.